Comparing Traditional Uses of Medicinal Plants for Malaria Treatment in Kabuula Sub-County Lyantonde District. - Kirya, Ali (Kabale University, 2025)
This study aimed to assess the medicinal plants used for malaria treatment and to evaluate the attitudes of residents towards these plants in Kaliiro and Kashagama parishes of Kabuula Sub County, Lyantonde District, Uganda. A mixed-methods approach was employed, combining quantitative data from field surveys with qualitative data from semi-structured interviews. A total of 12 medicinal plant species were identified, with Aloe barbadensis miller, Vernonia amygdalina, and Artemisia annua being the most frequently occurring and widely used species. Kaliiro Parish exhibited slightly higher species diversity (Shannon-Wiener Index, H' = 2.40) compared to Kashagama Parish (H' = 2.25), indicating a balanced distribution of medicinal plants across the study area. Interviews with 30 participants revealed strong cultural significance and trust in the efficacy of these plants, particularly for treating malaria. However, concerns were raised about the erosion of traditional knowledge and the potential loss of medicinal plant diversity. The study concludes that while medicinal plants remain crucial for malaria treatment in these communities, there is a pressing need for conservation efforts, documentation of traditional knowledge, and further research into the efficacy of these plants. Recommendations include promoting sustainable harvesting practices, enhancing community awareness, and exploring the integration of traditional and modern medicine.